Analysing the Potential of Pesantren as an Agent of Inter-Religious Harmony - Rahman, Fazlul; Mala, Faiqotul; Dianta, Dedon (Religió Jurnal Studi Agama-agama, 2022)
This article attempts to look at great potential of pesantren as the oldest Islamic religious institution in Indonesia. This research analyzes the three primary assets owned by pesantren (human capital, social capital, and intellectual capital) to become agents of inter-religious harmony. It is based on field research conducted in two Islamic boarding schools with great attention to issues of inter-religious harmony, namely the Aswaja Nusantara Islamic Boarding School, Mlangi, Yogyakarta, managed by Kiai Muhammad Mustafid and the Roudhatus Sholihin Islamic Boarding School, Demak, managed by KH. Abdul Qodir, Lc. The primary data sources of this study were taken from interviews with the leaders and notes from Focus Group Discussions (FGD) with representatives of students. Based on the SWOT analysis of the collected data, this study concludes that Pesantren has excellent potential to become an agent of inter-religious harmony because of its social and intellectual capital and the diverse backgrounds of its students. However, this still requires pesantrens to conduct collaborative-comprehensive efforts to maximize their potential.